Organizational Culture and Job Satisfaction in Bank: Perceptions and Reactions of Employees - Hakim, Md. Abdul (Global Disclosure of Economics and Business, 2015)
This study examines employees’ perceptions and reactions regarding the organizational culture for their job satisfaction where the five variables or organizational culture are selected as working conditions, compensations, respect from co-workers, relationships with supervisors and opportunity for advancement. The key purpose of this study effort was to investigate how organizational culture can affect job satisfaction of the employees in response their perceptions and reactions towards the organizational culture factors. This study operationally defined culture in terms of working conditions, compensations and benefits, respect from co-workers, relationships with supervisors and opportunity for advancement. To this research, both primary and secondary data are used where the statistical population included the employees of bank organizations in Bangladesh. Almost primary based, the data were collected through the distribution of a standardized questionnaire among 500 employees through convenience sampling. This study revealed that Respects from the co-workers as the components of organizational variable has the most domination in framing Job Satisfaction in respect of the employees perceptions of the bankers where working conditions has the least among five explanatory variables. The statistical result of this paper also found that the selected organizational culture related variables have the direct effect over the level of job satisfaction to either increase or decrease. The results of this study supported the reliability measures of the organizational culture questionnaire over the populations, regardless of the reality that the sample size for this study was inadequate. A further suggestion for future research would be to establish whether improving measurement and response mechanisms in the jobs of social workers would positively influence job satisfaction and perception of organizational culture by employees in this job category.